Multiple Organ Dysfunction Syndrome Secondary to Multiple Wasp Stings: A Case Report - Anh Tuan Mai; Duy Chung; Luan Ngo; Phuc Vu; Kim Huyen Huynh (Annals of Internal Medicine: Clinical Cases)
Wasp sting is common in resource-limited countries like Viet Nam. Symptoms can range from mild (itching, urticaria, and angioedema) to severe (multiorgan dysfunction), which increases mortality. Rhabdomyolysis and acute respiratory distress syndrome are rare complications but yield a high risk of death, thus requiring emergent interventions. We present a case of a 32-year-old man suffering from multiple wasp stings. The patient manifested several swollen, erythematous, and tender stings, and then developed a high fever, dyspnea, and reddish urine. He was diagnosed with multiple organ dysfunction syndrome, including severe hemolysis, acute kidney injury, liver injury, and acute respiratory distress syndrome.